Comparative Study of Early Versus Delayed Enteral Feeding in Development of Necrotizing Enterocolitis for Preterm Small for Date Babies (Bangladesh Journal of Child Health, 2018)
Background: Growth-restricted preterm infants are at increased risk of developing necrotizing enterocolitis (NEC) and initiation of enteral feeding is frequently delayed, even though delayed enteral feeding could diminish the functional adaptation of the gastrointestinal tract and result in feeding intolerance later.Objectives: To evaluate the development of necrotizing enterocolitis of early and delayed enteral feeding in preterm small for date babies (weighing 1000-1499 grams).Materials and Methods: This was a consecutive sampling technique, conducted in the Department of Paediatrics Sylhet MAG Osmani Medical College Hospital during the period from July 2012 to June 2014. One hundred and forty neonates with preterm small for date babies were selected according to inclusion and exclusion criteria. Inclusion criteria were baby born preterm (0.05], death [10 (16.7%) vs 11 (16.9%); p>0.05], oral feeding not established [1 (1.7%) vs 2 (3.1%); p>0.05], referred to paediatric surgery [4 (6.7%) vs 5 (7.7%); p>0.05] did not differ significantly between early and late feeding group. Causes of death were sepsis in 3 (30.0%), recurrent apnoea in 4 (40.0%)] and hypothermia in 3 (30.0%) in early feeding group; while causes of death were sepsis in 5 (45.5%), recurrent apnoea in 4 (36.4%)] and hypothermia in 2 (18.1%) neonates in late feeding group (p=0.861,p=0.881,p=0.781 respectively).Conclusion: Findings of this consecutive sampling technique concludes that early enteral feeding with breast milk does not increase the incidence of NEC, sepsis and death.Bangladesh J Child Health 2017; VOL 41 (2) :84-91